The Alleviation of Allocation Funding and Rural Poverty in Indonesia - Ambya; Nairobi; Rizqiandri, Muhammad (International Journal of Economics, Business, and Entrepreneurship, 2019)
Indonesian authority put the fiscal decentralization as one of the policies established to delegate the authority of the central authority to each region to explore sources of income, to benefit the merit in receiving allocations from the higher level of authority, and to organize routine and investment spending. Poverty alleviation is an important agenda for a country to realize the welfare of its people so that poverty alleviation becomes an abroad and massive issue in implementing Sustainable Development Goals (SDGs). This study aims to see how big the influence of fiscal decentralization is, in terms of authority spending, in the form the allocation funding consisting of the General Allocation Funding (DAU), the Special Allocation Funding (DAK) and the Village Funding (DD) on the Poverty Rate in 34 provinces in Indonesia. This paper used a dynamic panel data analysis through the approach Generalized Method of Moment (GMM). The results of this study concluded that the DAU, DAK, and Village Funding variables becoming significantly influencing the rural poverty reduction in Indonesia.